The Effect of WPM (Woody Potent Medium) Dosage on the In Vitro Development of Milo Pace Variety Robusta Coffee Leaf Explants: Pengaruh Dosis Media WPM (Woody Pant Medium) Terhadap Perkembangan Eksplan Daun Kopi Robusta Varietas Milo Pace Secara In Vitro - Rana Az Zahra; Muhammad Burhanuddin Irsyadi; Dwi Erwin Kusbianto; Hasbi Mubarok Suud; Muhammad Ghufron Rosyadi; Distian Wulanjari; Oria Alit Farisi (Jurusan Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Timor, 2025)
Milo pace robusta coffee is a local coffee variety in Jember Regency that is threatened with extinction. One way to overcome this problem is by propagating it through tissue culture. The success of tissue culture is determined by the use of optimal culture media doses. Research related to the development of Milo pace coffee is still very limited. This study aims to obtain the best dose in woody plant medium media for the development of robusta coffee leaf explants of the Milo pace variety. This study used a completely randomized design (CRD) with a single factor, namely the WPM media dose (1 time, ¾ times, ½ times and MS 1 time as a control) which was repeated 3 times with 3 samples. Data were analyzed descriptively and statistically using analysis of variance, and continued with the DMRT test at a 95% confidence level. The results showed that the use of WPM media with 1 dose was the best dose with a percentage of imbibed explants of 77.77% with an average emergence at 2.53 ± 0.68 DAI and green live explants. Furthermore, the percentage of browning explants was still high at 88.89±19.24%, which appeared at 9.96±1.73 DAI. Various doses of WPM media were unable to induce callus in Milo Pace robusta coffee leaf explants.